ANALISIS TINGKAT KEUNTUNGAN KAYU GERGAJIAN PADA CV. LIANG RAYA DI DESA LIANG KECAMATAN TELUK ELPAPUTIH KABUPATEN MALUKU TENGAH - Rehatta, Cici Dwi Astuti; Siahaya, Troice Else; Marasabessy, Husain (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This study aims to analyze the profit level of sawn timber business at CV. Liang Raya, located in Liang Village, Teluk Elpaputih District, Central Maluku Regency. The sawn timber industry plays an important role in supporting regional economic development, yet its sustainability highly depends on raw material availability, production costs, and management strategies. Data were collected through interviews, direct observation, and secondary sources from company reports and related institutions. The analysis was carried out quantitatively by calculating production costs, revenues, and profits during the period of March 2019 to February 2020. The results showed that the total production cost incurred by the company amounted to IDR 1,735,258,988, consisting of fixed costs of IDR 303,475,000 and variable costs of IDR 1,431,784,000. The total revenue from sawn timber sales reached IDR 3,154,300,000. Thus, the net profit obtained by CV. Liang Raya was IDR 1,419,041,012. Monthly profit varied, with the highest recorded in May 2019 at IDR 142,932,751 and the lowest in February 2020 at IDR 102,400,751. These findings highlight that production cost efficiency and the availability of raw materials are key factors in determining the sustainability of local sawn timber enterprises.